The Concept of â€œBebarenganâ€ That Construct The Spatial Identity of Dinoyo Ceramic Village - Cyntha Tendean; Wara Indira; Turniningtyas Turniningtyas (Sekolah Pascasarjana Universitas Brawijaya, 2018)
Dinoyo Ceramic Village of Malang City is a village that has distinctive community socio-cultural and economic characteristics. Almost all of the community of Dinoyo Ceramic Village work as ceramic makers and traders from generation to generation. Dinoyo Ceramic Village has a history well-known for its ceramic industry that has existed since the 1950s and supposedly the community ability to make ceramics has emerged since the days of the Kingdom of Kanjuruhan in the 8th century AD. This study aimed to reveal the space identity themes formed by physical and socio-economic elements and to disclose the concept of space identity or genius loci of Dinoyo Ceramic Village. This study used a descriptive explorative method with a narrative descriptive analysis technique. The results showed that the space identity themes constructed from the physical and socio-economic elements are â€œJagonganâ€ Space, â€œBaleâ€ Space, â€œBebarenganâ€ Space, and â€œDodolanâ€ Space. â€œBebarenganâ€ is one of the space identity concepts in Dinoyo Ceramic Village. â€œBebarenganâ€ is defined as a unity or togetherness found in the terns of Activities, Performers, Space Quality, Elements, and Space Settings.